THE DEVELOPMENT OF AN INTERACTIVE MULTIMEDIA COURSEWARE TO APGRADE ANALITYCAL THINGKING SKILLS VIA INQUARY-BASED LEARNING APPROACH IN BASIC SCHOOL - Arifin, Arifin (Infoman's, 2009)
In Indonesia, limited amount of research has been done to investigate analytical thinking capabilities of student from the point of view of inquiry-based learning approach. In view of the objectives of the present educational system to develop the quality manpower for it to enter new knowledge era, better understanding of the resourcefullness of Indonesia students and factors which could affect or enhance it becomes more crusial. The possibility of integrating interactive multimedia technology into the teaching of thinking skills via the school-based network system that is already in placed in Indonesian smart schools today would be of concern to the educator and policy makers